A community-oriented survey on the association between androgenetic alopecia and metabolic syndrome in Chinese people - Zhu, Hongliu; Guo, Haijian; Gao, Yihong; Wei, Yuegang; Mao, Tao; Yang, Jianqiu (Frontiers in Medicine, 2022)
Background: Several studies on Caucasians have revealed a positive relationship between androgenetic alopecia (AGA) and metabolic syndrome. However, this correlation varies in different contexts. Currently, the association of AGA with metabolic syndrome is yet to be studied and elucidated in Chinese people. Objective: To evaluate the association between AGA and metabolic syndrome in the Chinese population. Methods: This study included information on components of metabolic syndrome along with other possible risk factors in a total of 3703 subjects. The patients’ loss of hair was assessed using Hamilton-Norwood and Ludwig classification method. Results: In this study, 29.88% of male and 27.58% of female AGA patients were diagnosed with metabolic syndrome, while the rest were regarded as controls (29.95% of male and 27.89% of female control subjects) (P>0.05). The AGA males presented significantly higher systolic and diastolic blood pressure than the male control subjects (SP: P=0.000; DP: P=0.041). Among females with AGA, waist circumference, hip circumference, and waist-hip ratio elevated the loss of hair compared to that of the female controls (P=0.000, 0.020, 0.001, respectively). Conclusion: Our study indicated no direct association between AGA and metabolic syndrome in Chinese people. However, a close relationship was observed between AGA and systolic blood pressure.